AN OVERVIEW OF STRUCTURAL HEALTH MONITORING BY USING SMART SENSING TECHNOLOGY – “A REVIEW” - Ashokkumar Palanisamy, Dr. D.Jegatheeswaran, Saranya Sampath (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
In the present growing technology, the continuous monitoring of structures has been easier task by using the various sensor techniques and Internet of Things technology to ensure the safety and strength of the structures. All the structures will get degrade and deteriorate with increase in time due to loadings, corrosion and other factors. To implement the continuous monitoring system for the structures, the Sensors are plays major role for the monitoring process. Due to various continuous environment and climatic changes, the strength and durability of the structures are severely affected and the damage deduction inside the concrete structure is becomes a very monotonous process. The various non destructive testing methods were used to find the strength, damage and durability assessment in the existing and proposed concrete structures. In the destructive testing methods, the assessment is carried out near by the concrete damaged structures by direct contact which may cause adverse effect. By using modern technology, nowadays non destructive and non contact methods have been implementing to deduct the various parameters of the concrete structures by using modern sensors. This review paper gives the overview about the sensors and explains the various practical applications of sensors in the concrete structures to identify the problems by using modern sensors like piezoelectric sensor, Wireless sensor, and smart aggregate to deduct the concrete strength, rate of corrosion, cracks, and strain deflection of the structures